Direct current therapy with/without lidocaine iontophoresis in myofascial pain syndrome - Kaya, Arzu; Kamanli, Ayhan; Ardicoglu, Ozge; Ozgocmen, Salih; Ozkurt-Zengin, Fatma; Bayik, Yilmaz (My University, 2009)
Objectives: This study aimed to assess the effectiveness of lidocaine iontophoresis for inactivation of trigger points (TrPs) in the treatment of myofascial pain syndrome (MPS). Methods: Fifty-eight trigger points (cervical and/or periscapular regions) in 18 female and 2 male patients with MPS were randomly assigned to two groups. These groups were treated with: lidocaine iontophoresis using direct current (3 mA, 10 min) (n: 10, 28 TrPs) or only direct current (n: 10, 30 TrPs). Lidocaine iontophoresis or direct current, followed by stretching and strengthening exercises of each of the involved muscles and postural exercises were given in both groups once daily for ten days. Clinical assessment including cervical range of motion (ROM), TrP pain pressure threshold (PPT) measurement, and manual pain scores (PS), Visual analogue scale-pain (VAS-pain), fatigue and work disability scores were evaluated at baseline, at the end of a 10 session course of treatment and at the end of fourth week. Additionally, Hamilton depression and anxiety rating scales and Nottingham Health Profile (NHP) were used to evaluate and assess depression and anxiety and quality of life, respectively. The subjects were also asked to describe their side effects. Results: PPT, pain scores, VAS-pain were significantly improved in both groups at the end of treatment and during evaluation at fourth week. The improvement of these parameters was not significantly different between groups at the end of treatment. Quality of life (NHP scores) (p<0.016) and depression and anxiety scores (p<0.05) significantly improved with treatment in both groups. Conclusion: Direct current therapy with/without lidocaine iontophoresis were determined to be effective treatment modalities in TrP management. These treatment modalities are non-invasive, cost effective and provide long term improvement. Thus, these modalities could be safely used in the management of MPS with minimal side effects, particularly if patients may not accept injection or other treatments.
Keywords: Galvanic current; Lidocaine iontophoresis; Myofascial pain syndrome; Trigger point management